A study in identifying factors in YouTube advertisements that influence consumer purchasing behaviour among people in Malaysia - Ho, Sing Yee; Lau, Qian Yu; Yeo, Yi Wei (2020)
Nowadays online advertising has grown rapidly to attract a large amount of targeted audiences. YouTube has become one of the popular platforms for advertisers and marketers to promote their brand, products or services. However, there are advertisements considered as ineffective in leading consumer purchasing behaviour due to the majority of them tend to skip or ignore advertisements on Youtube. Thus, this research paper aims to identify the factors in YouTube advertisement that influence the consumer purchasing behaviour among people in Malaysia. It discussed about the 4 factors adopted in YouTube advertisement which included Celebrity Endorsement, Emotional Appeal, Sales Promotion and Brand Image. This study focused on understanding the opinions of an individual by utilizing qualitative research and in-depth online interviews to study the problem statement. There are a total of 15 interviewees who have personal experiences on streaming YouTube chosen for online interview sessions. The data collected analyzed by using thematic analysis in this study. In conclusion, sales promotion is considered as the most effective factor that should be included in Youtube advertisements in affecting consumers to be aware of brands and products they are not familiar with, and hence influence their purchasing behaviour effectively. There is conclusion, some limitations and recommendations included in this research to provide overall directions for researchers in conducting future study in related fields.